Informality and Profitability : Evidence from a New Firm Survey in Ecuador - Medvedev, Denis; Oviedo, Ana María (Taylor and Francis, 2015)
This article estimates the impact of informality on profits using a new survey administered to 1,200 firms with less than 50 employees in four cities in Ecuador. The article proposes a novel definition of informality which explicitly recognises that most firms comply with some regulations but not others. Accounting for firm selection and controlling for a large set of firm, owner and location characteristics, the article finds that more formal firms tend to be more profitable and have higher output per worker. This impact operates, inter alia, through improved access to credit and higher sales through issuance of tax receipts.